Digital Transformation and Its Role in Enhancing Supply Chain Efficiency - Erik Lundström; Freja Jansson; Magnus Andersson (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article examines how digital transformation, including the use of big data, Internet of Things (IoT), and blockchain, enhances supply chain efficiency. Focusing on the retail and manufacturing sectors, the study reveals that digital tools improve visibility, reduce delays, and optimize inventory management. The findings suggest that digital transformation is essential for businesses aiming to increase agility and resilience in a globalized supply chain.